Spontaneous activity in the waiting brain: A marker of impulsive choice in attention-deficit/hyperactivity disorder? - Hsu, Chia-Fen (Dev Cogn Neurosci, 2015)
BACKGROUND: Spontaneous very low frequency oscillations (VLFO), seen in the resting brain, are attenuated when individuals are working on attention demanding tasks or waiting for rewards (Hsu et al., 2013). Individuals with attention-deficit/hyperactivity disorder (ADHD) display excess VLFO when working on attention tasks. They also have difficulty waiting for rewards. Here we examined the waiting brain signature in ADHD and its association with impulsive choice. METHODS: DC-EEG from 21 children with ADHD and 21 controls (9–15 years) were collected under four conditions: (i) resting; (ii) choosing to wait; (iii) being “forced” to wait; and (iv) working on a reaction time task. A questionnaire measured two components of impulsive choice. RESULTS: Significant VLFO reductions were observed in controls within anterior brain regions in both working and waiting conditions. Individuals with ADHD showed VLFO attenuation while working but to a reduced level and none at all when waiting. A closer inspection revealed an increase of VLFO activity in temporal regions during waiting. Excess VLFO activity during waiting was associated with parents’ ratings of temporal discounting and delay aversion. CONCLUSIONS: The results highlight the potential role for waiting-related spontaneous neural activity in the pathophysiology of impulsive decision-making of ADHD.